A method for preparing molybdenum sulfide-coated barium titanate nanofibers

Molybdenum sulfide-coated barium titanate nanofibers were prepared by sol-gel method and electrospinning technology, which solved the problem of thermal concentration of barium titanate materials in capacitors, and achieved high energy storage and wide temperature stability dielectric capacitor performance.

CN116590809BActive Publication Date: 2025-05-02SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310731397.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-05-02
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

During the charging and discharging of capacitors, barium titanate materials are prone to thermal concentration, resulting in attenuation of energy storage performance, and it is difficult to build a stable framework between molybdenum sulfide and barium titanate through traditional solution mixing methods.

Method used

Molybdenum sulfide was dispersed by sol-gel method, and synthesized with barium titanate gel through coaxial electrospinning technology. Then, heat treatment was performed to remove impurities such as tackifiers to prepare molybdenum sulfide-coated barium titanate nanofibers.

Benefits of technology

The prepared molybdenum sulfide coated barium titanate nanofiber has excellent dielectric properties and thermal conductivity, and can show good stability in the fields of high energy storage and wide temperature frequency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116590809B_ABST
    Figure CN116590809B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of molybdenum sulfide coated barium titanate, and in particular to a method for preparing molybdenum sulfide coated barium titanate nanofibers. The preparation method provided by the present invention comprises the following steps: firstly mixing a titanium source, a barium source, acetic acid, acetylacetone, water and a first thickener to obtain a first spinning solution; secondly mixing molybdenum sulfide, a dispersion medium and a second thickener by a sol-gel method to obtain a second spinning solution; using the first spinning solution as an inner core layer and the second spinning solution as an outer shell layer, spinning the first spinning solution and the second spinning solution by coaxial electrostatic spinning, and then heat treating to obtain the molybdenum sulfide coated barium titanate nanofibers. The preparation method can greatly promote the growth of the skeleton between molybdenum sulfide and barium titanate, and the prepared molybdenum sulfide coated barium titanate nanofibers have excellent dielectric properties and thermal conductivity, and have good stability in the fields of high energy storage and wide temperature frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molybdenum sulfide-coated barium titanate, and in particular to a method for preparing molybdenum sulfide-coated barium titanate nanofibers. Background Art

[0002] With the development of the power electronics industry, 5G is widely used in daily communications and other fields. Microelectronic devices are developing rapidly in the direction of lightweight and miniaturization. At the same time, higher requirements are placed on the electrical and thermal conductivity of electronic components and various energy storage materials. Among the many choices, two-dimensional molybdenum sulfide materials have aroused widespread research interest with their unique electrical, thermal, physical and chemical properties. During the charging and discharging process of the capacitor, barium titanate as a filler is prone to heat concentration, which makes the polymer matrix prone to aging and leads to the attenuation of energy storage performance. However, through the coating of molybdenum sulfide, a heat transfer channel can be constructed on the surface of the barium titanate material, which greatly improves the application range of the capacitor in a wide temperature range. Based on the extremely stable structure of barium titanate and molybdenum sulfide themselves, the traditional solution mixing method cannot perfectly build a skeleton between the two to achieve the purpose. Electrospinning can be tried to prepare a stable skeleton structure. However, molybdenum sulfide is composed of three atomic layers (S-Mo-S) and has strong rigidity, so it is still a challenge to build a skeleton between molybdenum sulfide and barium titanate. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing molybdenum sulfide-coated barium titanate nanofibers, which can greatly promote the growth of the skeleton between molybdenum sulfide and barium titanate. The prepared molybdenum sulfide-coated barium titanate nanofibers have excellent dielectric properties and thermal conductivity, and have good stability in the fields of high energy storage and wide temperature frequency.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing molybdenum sulfide-coated barium titanate nanofibers, comprising the following steps:

[0006] The titanium source, the barium source, the acetic acid, the acetylacetone, the water and the first thickener are first mixed to obtain a first spinning solution;

[0007] Molybdenum sulfide, a dispersion medium and a second viscosity enhancer are mixed by a sol-gel method to obtain a second spinning solution;

[0008] The first spinning solution is used as the inner core layer, and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are spun by coaxial electrospinning, and then heat treated to obtain the molybdenum sulfide-coated barium titanate nanofibers.

[0009] Preferably, the titanium source includes one or more of tetrabutyl titanate, isobutyl titanate, tetraethyl titanate and polybutyl titanate;

[0010] The barium source includes one or more of barium acetate, barium sulfate, barium phosphate, barium oxalate, barium perchlorate and barium metaphosphate;

[0011] The first tackifier and the second tackifier independently include one or more of polystyrene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polylactic acid.

[0012] Preferably, the mass ratio of acetylacetone, titanium source, barium source, acetic acid and water is 1:(1-100):(1-100):(1-100):(1-100).

[0013] Preferably, the mass ratio of the first viscosity enhancer to the titanium source is 1:(1-100).

[0014] Preferably, the mass ratio of the second viscosity enhancer to molybdenum sulfide is 10:(1-20).

[0015] Preferably, the dispersion medium comprises acetic acid and / or ethanol;

[0016] The mass ratio of the molybdenum sulfide to the dispersion medium is 1:(10-100).

[0017] Preferably, the first mixing and the second mixing are performed under stirring conditions;

[0018] The stirring speed is 300-1000 rpm, the time is 1-10 hours, and the temperature is 20-150°C.

[0019] Preferably, the spinning conditions of the first spinning solution are: spinning rate of 0.1-3 mL / h, voltage of 10-30 kV, temperature of 20-60° C., humidity of 20-60%, and spinning distance of 8-30 cm.

[0020] Preferably, the spinning conditions of the second spinning solution are: spinning rate of 0.1-30 mL / h, voltage of 10-30 kV, temperature of 20-60° C., humidity of 20-60%, and spinning distance of 8-30 cm.

[0021] Preferably, the heat treatment is carried out in a protective atmosphere;

[0022] The heat treatment temperature is 500-950° C. and the time is 0.5-6 hours.

[0023] The present invention provides a method for preparing molybdenum sulfide coated barium titanate nanofibers, comprising the following steps: firstly mixing a titanium source, a barium source, acetic acid, acetylacetone, water and a first thickener to obtain a first spinning solution; secondly mixing molybdenum sulfide, a dispersion medium and a second thickener by a sol-gel method to obtain a second spinning solution; using the first spinning solution as an inner core layer and the second spinning solution as an outer shell layer, spinning the first spinning solution and the second spinning solution by coaxial electrostatic spinning, and then heat treating to obtain the molybdenum sulfide coated barium titanate nanofibers. The present invention firstly disperses molybdenum sulfide by a sol-gel method, and then synthesizes it with barium titanate gel by electrostatic spinning technology, and then removes impurities such as thickeners by heat treatment, and finally obtains the target product; the molybdenum sulfide coated barium titanate nanofibers prepared by the preparation method have a regular and uniform skeleton, and the outer layer of molybdenum sulfide is relatively thin; at the same time, it has excellent dielectric properties and thermal conductivity, and can be applied to high energy storage and wide temperature frequency dielectric capacitors. The present invention has the characteristics of simplicity, easy operation and control.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The sources of molybdenum sulfide, titanium source and barium source are extensive and inexpensive;

[0026] There are many types of thickeners, which are inexpensive and have good viscosity effects, and are conducive to the construction of the framework between molybdenum sulfide and barium titanate;

[0027] Large-scale preparation can be achieved through electrospinning, which is easy to scale up production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the X-ray diffraction pattern of the molybdenum sulfide-coated barium titanate nanofiber film described in Example 1;

[0029] Figure 2 This is the FTIR spectrum of the molybdenum sulfide coated barium titanate nanofiber film described in Example 1;

[0030] Figure 3 This is a scanning electron microscope image of the molybdenum sulfide-coated barium titanate nanofiber film described in Example 1;

[0031] Figure 4 This is a transmission electron microscopy image of the molybdenum sulfide-coated barium titanate nanofiber film described in Example 1. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing molybdenum sulfide-coated barium titanate nanofibers, comprising the following steps:

[0033] The titanium source, the barium source, the acetic acid, the acetylacetone, the water and the first thickener are first mixed to obtain a first spinning solution;

[0034] Molybdenum sulfide, a dispersion medium and a second viscosity enhancer are mixed by a sol-gel method to obtain a second spinning solution;

[0035] The first spinning solution is used as the inner core layer, and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are spun by coaxial electrospinning, and then heat treated to obtain the molybdenum sulfide-coated barium titanate nanofibers.

[0036] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0037] The present invention first mixes a titanium source, a barium source, acetic acid, acetylacetone, water and a first viscosity enhancer to obtain a first spinning solution.

[0038] In the present invention, the titanium source preferably includes one or more of tetrabutyl titanate, isobutyl titanate, tetraethyl titanate and polybutyl titanate. When the titanium source is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0039] In the present invention, the barium source preferably includes one or more of barium acetate, barium sulfate, barium phosphate, barium oxalate, barium perchlorate and barium metaphosphate. When the barium source is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0040] In the present invention, the water is preferably deionized water.

[0041] In the present invention, the first thickener preferably includes one or more of polystyrene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polylactic acid. When the first thickener is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0042] In the present invention, the mass ratio of acetylacetone, titanium source, barium source, acetic acid and water is preferably 1: (1-100): (1-100): (1-100): (1-100), more preferably 1: (10-80): (10-80): (10-80): (10-80), and most preferably 1: (30-50): (30-50): (30-50): (30-50). In the present invention, the mass ratio of the first tackifier and the titanium source is preferably 1: (1-100), more preferably 1: (10-80), and most preferably 1: (10-50).

[0043] In the present invention, the acetic acid serves as a buffer solution to promote the reaction between the barium source and the titanium source; and the acetylacetone serves to increase the surface tension of the mixed solution.

[0044] In the present invention, the first mixing is preferably carried out under stirring conditions; the stirring speed is preferably 300-1000 rpm, more preferably 400-800 rpm, most preferably 500-600 rpm; the time is preferably 1-10 h, more preferably 2-8 h, most preferably 4-6 h; the temperature is preferably 20-150° C., more preferably 50-130° C., most preferably 80-100° C.

[0045] After the first mixing is completed, the present invention also preferably includes ultrasound, standing and defoaming treatments performed in sequence. The present invention does not have any special limitation on the processes of ultrasound, standing and defoaming treatments, and the processes well known to those skilled in the art can be used.

[0046] After obtaining the first spinning solution, the present invention uses a sol-gel method to mix molybdenum sulfide, a dispersion medium and a second viscosity enhancer to obtain a second spinning solution.

[0047] In the present invention, the particle size of the molybdenum sulfide is preferably 10 nm to 2 μm.

[0048] In the present invention, the dispersion medium preferably includes acetic acid and / or ethanol.

[0049] In the present invention, the second thickener preferably includes one or more of polystyrene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polylactic acid. When the second thickener is two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio.

[0050] In the present invention, the mass ratio of the second viscosity enhancer to molybdenum sulfide is preferably 10:(1-20), more preferably 10:(3-15), and most preferably 10:(3-10).

[0051] In the present invention, the mass ratio of the molybdenum sulfide to the dispersion medium is preferably 1:(10-100), more preferably 1:(20-80), and most preferably 1:(20-40).

[0052] In the present invention, the second mixing is preferably carried out under stirring conditions; the stirring speed is preferably 300-1000 rpm, more preferably 400-800 rpm, most preferably 500-600 rpm; the time is preferably 1-10 h, more preferably 2-8 h, most preferably 4-6 h; the temperature is preferably 20-150° C., more preferably 50-130° C., most preferably 80-100° C.

[0053] After the second mixing is completed, the present invention further preferably includes ultrasonic oscillation. The present invention has no special limitation on the process of ultrasonic oscillation, and the process well known to those skilled in the art can be used.

[0054] After obtaining the first spinning solution and the second spinning solution, the first spinning solution is used as the inner core layer and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are spun by coaxial electrospinning, and then heat treated to obtain the molybdenum sulfide-coated barium titanate nanofibers.

[0055] In the present invention, the spinning conditions of the first spinning solution are preferably: the spinning rate is preferably 0.1-3 mL / h, more preferably 0.5-2.5 mL / h, and most preferably 1.0-2.0 mL / h; the voltage is preferably 10-30 kV, more preferably 15-25 kV, and most preferably 18-22 kV; the temperature is preferably 20-60°C, more preferably 30-50°C, and most preferably 35-45°C; the humidity is preferably 20-60%, more preferably 30-50%, and most preferably 35-45%; the spinning distance is preferably 8-30 cm, more preferably 10-25 cm, and most preferably 15-20 cm.

[0056] In the present invention, the spinning conditions of the second spinning solution are preferably: the spinning rate is preferably 0.1-30 mL / h, more preferably 10-25 mL / h, and most preferably 15-20 mL / h; the voltage is preferably 10-30 kV, more preferably 15-25 kV, and most preferably 18-22 kV; the temperature is preferably 20-60°C, more preferably 30-50°C, and most preferably 35-45°C; the humidity is preferably 20-60%, more preferably 30-50%, and most preferably 35-45%; the spinning distance is preferably 8-30 cm, more preferably 10-25 cm, and most preferably 15-20 cm.

[0057] After the spinning is completed, the present invention also preferably includes drying, and the drying temperature is preferably 50-130° C., more preferably 60-100° C., most preferably 70-80° C.; the drying time is preferably 1-24 h, more preferably 5-20 h, most preferably 10-15 h.

[0058] In the present invention, the heat treatment is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably one or more of a nitrogen atmosphere, an argon atmosphere and a helium atmosphere; when the protective atmosphere is two or more of the above-mentioned specific options, the present invention has no special limitation on the ratio of the above-mentioned specific atmospheres.

[0059] In the present invention, the heat treatment temperature is preferably 500-950°C, more preferably 600-900°C, most preferably 700-800°C; the time is preferably 0.5-6h, more preferably 1-5h, most preferably 2-4h.

[0060] In the present invention, the heat treatment is used to promote the reaction between the barium source and the titanium source to synthesize barium titanate and to promote the thermal decomposition of residual organic matter.

[0061] The preparation method of the molybdenum sulfide coated barium titanate nanofibers provided by the present invention is described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.

[0062] Note: MoS2 was purchased from Shanghai Asma Materials Co., Ltd. with a particle size of 100 nm; barium acetate, acetic acid, acetylacetone, and tetrabutyl titanate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the morphology of the fiber film after spinning of the present invention was observed using a transmission electron microscope (JEM 2100F, JEOL, Japan). The crystal structure and phase analysis of BT and MoS2@BT-NFs were studied using an X-ray diffractometer (XRD, Bruker, Germany). The absorption spectra of MoS2 and MoS2@BT-NFs were studied using Fourier transform infrared spectroscopy;

[0063] Example 1

[0064] Under heating and stirring conditions (temperature of 90° C., rotation speed of 600 r / min), tetrabutyl titanate, barium acetate, acetylacetone and deionized water were dispersed in 10 g of acetic acid in a mass ratio of 6.4:4.8:1:1, stirred for 1 h, 0.3 g of polyvinyl pyrrolidone (10% relative to the mass of tetrabutyl titanate) was added, and ultrasonic treatment, standing and defoaming treatment were carried out in sequence to obtain a first spinning solution (barium titanate spinning solution);

[0065] Under heating and stirring conditions (temperature of 50° C., rotation speed of 600 r / min), 0.3 g of molybdenum sulfide was uniformly dispersed in 20 g of acetic acid, 1 g of polyvinyl pyrrolidone was added, and the stirring time was 2 h to obtain a second spinning solution (molybdenum sulfide spinning solution);

[0066] The first spinning solution is used as the inner core layer, and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are respectively spun simultaneously in different syringes (voltage is 15 kV, temperature is 35° C., humidity is 45%, and spinning distance is 10 cm; the spinning rate of the first spinning solution is 0.2 mL / h, and the spinning rate of the second spinning solution is 0.4 mL / h), then dried at 80° C. for 2 h, and heat treated (nitrogen atmosphere, 800° C., 2 h) to obtain the molybdenum sulfide-coated barium titanate nanofiber film (MoS2@BT-NFs film);

[0067] Figure 1 is the X-ray diffraction pattern of the molybdenum sulfide-coated barium titanate nanofiber film, Figure 2 is the FTIR spectrum of the molybdenum sulfide coated barium titanate nanofiber film, Figure 1 It can be seen that the molybdenum sulfide coated barium titanate nanofiber film presents a distinct crystalline structure without obvious stray peaks. In addition, the molybdenum sulfide coated barium titanate nanofiber film has four peaks at 31.6°, 38.9°, 45.2°, 56.1° and 65.8°, corresponding to the (110), (111), (200), (211) and (220) crystal planes of BaTiO3, respectively. A new characteristic peak appears at 14.5°, which belongs to the (002) crystal plane of MoS2, further indicating that MoS2 has been successfully coated on the surface of barium titanate;

[0068] Depend on Figure 2 It can be seen that the molybdenum sulfide coated barium titanate nanofiber film has a -1 、547cm -1 and 467cm -1 Obvious absorption peaks appear at the positions corresponding to CO bonds, Ti-O bonds and S-Mo bonds, respectively; molybdenum sulfide and barium titanate exist simultaneously in the molybdenum sulfide-coated barium titanate nanofiber film, and impurities are completely removed after heat treatment;

[0069] Figure 3 is a scanning electron microscope image of the molybdenum sulfide coated barium titanate nanofiber film, Figure 3 It can be seen that the surface of the molybdenum sulfide-coated barium titanate nanofiber film has a small number of holes, which is attributed to the fact that a small amount of molybdenum sulfide cannot completely coat the barium titanate;

[0070] Figure 4 is a transmission electron microscope image of the molybdenum sulfide coated barium titanate nanofiber film, Figure 4 It can be seen that the molybdenum sulfide in the molybdenum sulfide-coated barium titanate nanofiber film is successfully coated on the surface of the barium titanate.

[0071] Example 2

[0072] Under heating and stirring conditions (temperature of 90°C, rotation speed of 600r / min), tetrabutyl titanate, barium acetate, acetylacetone and deionized water in a mass ratio of 6.4:4.8:1:1 were dispersed in 10g of acetic acid, stirred for 1h, and 0.3g of polyvinyl pyrrolidone (10% relative to the mass of tetrabutyl titanate) was added to obtain a first spinning solution (barium titanate spinning solution);

[0073] Under heating and stirring conditions (temperature of 50° C., rotation speed of 600 r / min), 0.5 g of molybdenum sulfide was uniformly dispersed in 20 g of acetic acid, 1 g of polyvinyl pyrrolidone was added, and the stirring time was 2 h to obtain a second spinning solution (molybdenum sulfide spinning solution);

[0074] The first spinning solution is used as the inner core layer, and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are respectively spun simultaneously in different syringes (voltage is 15 kV, temperature is 35° C., humidity is 45%, and spinning distance is 10 cm; the spinning rate of the first spinning solution is 0.2 mL / h, and the spinning rate of the second spinning solution is 0.4 mL / h), then dried at 80° C. for 2 h, and heat treated (nitrogen atmosphere, 800° C., 2 h) to obtain the molybdenum sulfide-coated barium titanate nanofiber film (MoS2@BT-NFs film);

[0075] The molybdenum sulfide coated barium titanate nanofiber film was subjected to XRD, FTIR, SEM, TEM and thermal conductivity tests, and the test results were as follows: the molybdenum sulfide coated barium titanate nanofiber film was composed of molybdenum sulfide and barium titanate, and no obvious impurity peaks appeared, indicating that the impurities were completely removed by heat treatment. Scanning electron microscopy showed that fewer holes were generated on the surface of the obtained sample, which was attributed to the fact that a small amount of molybdenum sulfide could not completely coat the barium titanate; transmission electron microscopy showed that molybdenum sulfide was successfully coated on the surface of the barium titanate.

[0076] Example 3

[0077] Under heating and stirring conditions (temperature of 90°C, rotation speed of 600r / min), tetrabutyl titanate, barium acetate, acetylacetone and deionized water in a mass ratio of 6.4:4.8:1:1 were dispersed in 10g of acetic acid, stirred for 1h, and 0.3g of polyvinyl pyrrolidone was added to obtain a first spinning solution (barium titanate spinning solution);

[0078] Under heating and stirring conditions (temperature of 50° C., rotation speed of 600 r / min), 0.7 g of molybdenum sulfide was uniformly dispersed in 20 g of acetic acid, 1 g of polyvinyl pyrrolidone was added, and the stirring time was 2 h to obtain a second spinning solution (molybdenum sulfide spinning solution);

[0079] The first spinning solution is used as the inner core layer, and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are respectively spun simultaneously in different syringes (voltage is 15 kV, temperature is 35° C., humidity is 45%, and spinning distance is 10 cm; the spinning rate of the first spinning solution is 0.2 mL / h, and the spinning rate of the second spinning solution is 0.4 mL / h), then dried at 80° C. for 2 h, and heat treated (nitrogen atmosphere, 800° C., 2 h) to obtain the molybdenum sulfide-coated barium titanate nanofiber film (MoS2@BT-NFs film);

[0080] The molybdenum sulfide coated barium titanate nanofiber film was subjected to XRD, FTIR, SEM, TEM and thermal conductivity tests, and the test results were as follows: the molybdenum sulfide coated barium titanate nanofiber film was composed of molybdenum sulfide and barium titanate, and no obvious impurity peaks appeared, indicating that the impurities were completely removed by heat treatment. Scanning electron microscopy showed that the surface of the obtained sample was smooth and no obvious holes were generated; transmission electron microscopy showed that molybdenum sulfide was successfully coated on the surface of barium titanate.

[0081] Example 4

[0082] Under heating and stirring conditions (temperature of 90°C, rotation speed of 600r / min), tetrabutyl titanate, barium acetate, acetylacetone and deionized water in a mass ratio of 6.4:4.8:1:1 were dispersed in 10g of acetic acid, stirred for 1h, and 0.3g of polyvinyl pyrrolidone was added to obtain a first spinning solution (barium titanate spinning solution);

[0083] Under heating and stirring conditions (temperature of 50° C., rotation speed of 600 r / min), 0.9 g of molybdenum sulfide was uniformly dispersed in 20 g of acetic acid, 1 g of polyvinyl pyrrolidone was added, and the stirring time was 2 h to obtain a second spinning solution (molybdenum sulfide spinning solution);

[0084] The first spinning solution is used as the inner core layer, and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are respectively spun simultaneously in different syringes (voltage is 15 kV, temperature is 35° C., humidity is 45%, and spinning distance is 10 cm; the spinning rate of the first spinning solution is 0.2 mL / h, and the spinning rate of the second spinning solution is 0.4 mL / h), then dried at 80° C. for 2 h, and heat treated (nitrogen atmosphere, 800° C., 2 h) to obtain the molybdenum sulfide-coated barium titanate nanofiber film (MoS2@BT-NFs film);

[0085] The molybdenum sulfide coated barium titanate nanofiber film was subjected to XRD, FTIR, SEM, TEM and thermal conductivity tests, and the test results were as follows: the molybdenum sulfide coated barium titanate nanofiber film was composed of molybdenum sulfide and barium titanate, and no obvious impurity peaks appeared, indicating that the impurities were completely removed by heat treatment. Scanning electron microscopy showed that the surface of the obtained sample was smooth and no obvious holes were generated; transmission electron microscopy showed that molybdenum sulfide was successfully coated on the surface of barium titanate.

[0086] Example 5

[0087] Under heating and stirring conditions (temperature of 90°C, rotation speed of 600r / min), tetrabutyl titanate, barium acetate, acetylacetone and deionized water in a mass ratio of 6.4:4.8:1:1 were dispersed in 10g of acetic acid, stirred for 1h, and 0.3g of polyvinyl pyrrolidone was added to obtain a first spinning solution (barium titanate spinning solution);

[0088] Under heating and stirring conditions (temperature of 50° C., rotation speed of 600 r / min), 1.1 g of molybdenum sulfide was uniformly dispersed in 20 g of acetic acid, 1 g of polyvinyl pyrrolidone was added, and the stirring time was 2 h to obtain a second spinning solution (molybdenum sulfide spinning solution);

[0089] The first spinning solution is used as the inner core layer, and the second spinning solution is used as the outer shell layer. The first spinning solution and the second spinning solution are respectively spun simultaneously in different syringes (voltage is 15 kV, temperature is 35° C., humidity is 45%, and spinning distance is 10 cm; the spinning rate of the first spinning solution is 0.2 mL / h, and the spinning rate of the second spinning solution is 0.4 mL / h), then dried at 80° C. for 2 h, and heat treated (nitrogen atmosphere, 800° C., 2 h) to obtain the molybdenum sulfide-coated barium titanate nanofiber film (MoS2@BT-NFs film);

[0090] The molybdenum sulfide coated barium titanate nanofiber film was subjected to XRD, FTIR, SEM, TEM and thermal conductivity tests, and the test results were as follows: the molybdenum sulfide coated barium titanate nanofiber film was composed of molybdenum sulfide and barium titanate, and no obvious impurity peaks appeared, indicating that the impurities were completely removed by heat treatment, and scanning electron microscopy showed that no obvious holes were generated in the obtained sample; transmission electron microscopy showed that molybdenum sulfide was successfully coated on the surface of barium titanate.

[0091] Comparative Example 1

[0092] Referring to Example 1, the difference is that after obtaining the first spinning solution, the first spinning solution is directly spun to obtain a BT-NFs film.

[0093] Comparative Example 2

[0094] Commercially available molybdenum sulfide.

[0095] Test Case

[0096] The molybdenum sulfide coated barium titanate nanofiber films described in Examples 1 to 5, the BT-NFs film described in Comparative Example 1, and the molybdenum sulfide described in Comparative Example 2 were tested for thermal conductivity and dielectric properties. The test results are shown in Table 1:

[0097] Table 1 Thermal conductivity and dielectric properties of the molybdenum sulfide coated barium titanate nanofiber films described in Examples 1 to 5, the BT-NFs film described in Comparative Example 1, and the molybdenum sulfide described in Comparative Example 2

[0098]

[0099]

[0100] As can be seen from Table 1, the dielectric constant of Example 1 is slightly lower than that of Comparative Example 1, but it exhibits excellent thermal conductivity (thermal conductivity is more than 3 times that of Comparative Example 1); compared with Example 2, although there is some sacrifice in thermal conductivity, it retains a very high dielectric constant, thereby being able to improve higher energy storage performance. Therefore, Example 1 has both high dielectric constant and high thermal conductivity, and has a wider application prospect in the fields of high energy storage, wide temperature frequency dielectric capacitors, etc.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the original invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing molybdenum sulfide-coated barium titanate nanofibers, characterized in that: The following steps are involved: The titanium source, the barium source, the acetic acid, the acetylacetone, the water and the first thickener are first mixed to obtain a first spinning solution; Molybdenum sulfide, a dispersion medium and a second viscosity enhancer are mixed by a sol-gel method to obtain a second spinning solution; The first spinning solution is used as the inner core layer, the second spinning solution is used as the outer shell layer, the first spinning solution and the second spinning solution are spun by coaxial electrospinning, and then heat treated to obtain the molybdenum sulfide-coated barium titanate nanofibers; The first tackifier and the second tackifier independently include one or more of polystyrene, polyvinylidene fluoride, polyethylene, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol and polylactic acid; The dispersion medium includes acetic acid and / or ethanol.

2. The preparation method according to claim 1, characterized in that The titanium source includes one or more of tetrabutyl titanate, isobutyl titanate, tetraethyl titanate and polybutyl titanate; The barium source includes one or more of barium acetate, barium sulfate, barium phosphate, barium oxalate, barium perchlorate and barium metaphosphate.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the acetylacetone, the titanium source, the barium source, the acetic acid and the water is 1:(1-100):(1-100):(1-100):(1-100).

4. The preparation method according to claim 3, characterized in that: The mass ratio of the first viscosity enhancer to the titanium source is 1:(1-100).

5. The preparation method according to claim 1, characterized in that: The mass ratio of the second viscosity enhancer to molybdenum sulfide is 10:(1-20).

6. The preparation method according to claim 1, characterized in that: The mass ratio of the molybdenum sulfide to the dispersion medium is 1:(10-100).

7. The preparation method according to claim 1, characterized in that: The first mixing and the second mixing are performed under stirring conditions; The stirring speed is independently 300-1000 rpm, the time is independently 1-10 hours, and the temperature is independently 20-150°C.

8. The preparation method according to claim 1, characterized in that: The spinning conditions of the first spinning solution are: spinning rate of 0.1-3 mL / h, voltage of 10-30 kV, temperature of 20-60° C., humidity of 20-60%, and spinning distance of 8-30 cm.

9. The preparation method according to claim 1, characterized in that: The spinning conditions of the second spinning solution are: spinning rate of 0.1-30 mL / h, voltage of 10-30 kV, temperature of 20-60° C., humidity of 20-60%, and spinning distance of 8-30 cm.

10. The preparation method according to claim 1, characterized in that: The heat treatment is carried out in a protective atmosphere; The heat treatment temperature is 500-950° C. and the time is 0.5-6 hours.

Citation Information

Patent Citations

  • Preparation method for barium titanate nanofiber arrayed in orientation mode

    CN105506783A

  • Molybdenum disulfide-coated carbon nanofiber used as negative electrode material for lithium-ion battery and preparation method of molybdenum disulfide-coated carbon nanofiber

    CN107681142A